EFFECT OF FRENCH BEAN SEED PROTEINASE INHIBITORS (FBPIS) ON TRYPSIN AND CHYMOTRYPSIN ACTIVITY, GROWTH AND DEVELOPMENT OF HELICOVERPA ARMIGERA (HUBNER) - S. RAMESH BABU,; B. SUBRAHMANYAM, (The Bioscan, 2012)
French bean proteinase inhibitors (FbPIs) were isolated by ammonium sulfate precipitation followed by chromatography on DEAE-Sephadex A-25 and resulted in a purification of 13.51 fold with a 11.34% yield. FbPIs had high stability at different pH values (2.0 to 10.0) except pH 5.0 and are thermolabile beyond 80oC for 10 minutes. FbPIs exhibited effective against total proteolytic activity and trypsin like activity, but did not show any inhibitory effect on chymotrypsin activity of midgut of H. armigera. The inhibition kinetics studies against H. armigera gut trypsin are of non-competitive type. FbPIs had high affinity for H. armigera gut trypsin. The purified PI proteins incorporated test diets showed significant reduction in mean larval and the 100% mortality in the total larval population of H. armigera. Bioassays suggested that FbPIs could be used as a tool in engineering crop plants, which might exhibit increased resistance against cotton bollworm.